If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(x + 12) + -3x = -50 Reorder the terms: -5(12 + x) + -3x = -50 (12 * -5 + x * -5) + -3x = -50 (-60 + -5x) + -3x = -50 Combine like terms: -5x + -3x = -8x -60 + -8x = -50 Solving -60 + -8x = -50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + -8x = -50 + 60 Combine like terms: -60 + 60 = 0 0 + -8x = -50 + 60 -8x = -50 + 60 Combine like terms: -50 + 60 = 10 -8x = 10 Divide each side by '-8'. x = -1.25 Simplifying x = -1.25
| 2/x-6=12 | | 25=10+5P | | 2/15=6/y-5 | | -10*1/2 | | -4s+3t=16 | | -3x=-15/8 | | (466.56)^1/2 | | (x-4)+8=2x | | -10=-2/9u | | 5x-3y=3x-2y+8 | | 16/9=4u | | 166/9=4u | | -0.7=a/3 | | f(x)=6x^2+2x^3 | | -7/10=a/3 | | -9y-2y-18=26 | | 20+(15-5)= | | 8(14X-4)=2(X+2) | | 4*9y= | | -9+-0.25x= | | x^3-4.5x^2+6X=0 | | 24-2x=28 | | 4(3-x)=-8 | | x+4(c+9)= | | 8y-3x=15 | | 12x^2+48x+20=0 | | 12x^2+48x+20=f(x) | | 10-1/p=3 | | 12x^2+48x+20=y | | 0.6(8)+-4.5= | | -17x/2=7 | | 5x-6(2/3)=9 |